Diagnosis and Treatment of Irritable Bowel Syndrome: Clinical Recommendations of the Russian Gastroenterological Association and Association of Coloproctologists of Russia - V. T. Ivashkin; I. V. Maev; Yu. A. Shelygin; E. K. Baranskaya; S. S. Belous; E. A. Belousova; A. G. Beniashvili; S. V. Vasilyev; A. V. Veselov; E. G. Grigoryev; N. V. Kostenko; V. N. Kashnikov; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim. Current clinical recommendations accentuate current methods for the diagnosis and treatment of irritable bowel syndrome (IBS).Key points. IBS is a functional bowel disorder manifested with recurrent, at least weekly, abdominal pain with the following attributes (any two leastwise): link to defecation, its frequency or stool shape. The symptoms are expected to persist for at minimum three months in a total six-month follow-up. Similar to other functional gastrointestinal (GI) disorders, IBS can be diagnosed basing on the patient symptoms compliance with Rome IV criteria, provided the absence of potentially symptom-causative organic GI diseases. Due to challenging differential diagnosis, IBS can be appropriately established per exclusionem, with pre-examination as follows: general and biochemical blood tests; tissue transglutaminase IgA/IgG antibody tests; thyroid hormones test; faecal occult blood test; hydrogen glucose/ lactulose breath test for bacterial overgrowth; stool test for enteric bacterial pathogens and Clostridium difficile A/B toxins; stool calprotectin test; abdominal ultrasound; OGDS, with biopsy as appropriate; colonoscopy with biopsy. The IBS sequence is typically wavelike, with alternating remissions and exacerbations often triggered by psychoemotional stress. Treatment of IBS patients includes dietary and lifestyle adjustments, various-class drug agents prescription and psychotherapeutic measures.Conclusion. Adherence to clinical recommendations can facilitate timely diagnosis and improve medical aid quality in patients with different clinical IBS variants.